The neoliberal roots of modern vaccine hesitancy - Chris Sanders; Kristin Burnett (Journal of Health and Social Sciences)
Popular resistance to vaccines is not a new phenomenon and has been widely documented by medical historians. The latest iteration of this resistance, however, is popularly referred to as ‘vaccine hesitancy’ and reflects a host of beliefs and social and institutional influences. While it may be tempting to dismiss the views of those who resist vaccines, immunization policies and practice cannot be devised in isolation from the contemporary political and social landscape. Understanding the socio-political meanings that lay people assign to vaccines and the manner in which they communicate these concerns via media is essential for public health practitioners to consider when formulating immunization policy and education praxis. One such meaning that, to date, has received relatively less attention is the socio-political ideology of neoliberalism. We argue that the undercurrent of neoliberal sensibilities expressed in media stories points to another key social factor that must be considered when seeking public health solutions to the growing vaccine hesitancy movement.